2023
DOI: 10.1108/tqm-05-2023-0147
|View full text |Cite
|
Sign up to set email alerts
|

Does integrated store service quality explain omnichannel shoppers' online brand advocacy behaviors?: role of memorable shopping experiences, store attachment, and relationship strength

Thamaraiselvan Natarajan,
Deepak Ramanan Veera Raghavan

Abstract: PurposeThe online brand advocacy behaviors of omnichannel shoppers, who mainly rely on integrated brick-and-mortar stores (recognized as a vital channel for delivering a seamless shopping experience and meeting the dynamic needs of the shoppers), are still understudied. This study aims to investigate how integrated store service quality (ISSQ) may elicit both positive and negative emotions that contribute to a memorable omnichannel shopping experience and have an impact on shoppers' attachment to the store, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…Brand attachment was found to have a positive effect on brand advocacy. This result supports previous studies [28,64,65,69] that identified the relationship between brand attachment and brand advocacy. Additionally, brand attachment was found to have a positive effect on brand loyalty.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Brand attachment was found to have a positive effect on brand advocacy. This result supports previous studies [28,64,65,69] that identified the relationship between brand attachment and brand advocacy. Additionally, brand attachment was found to have a positive effect on brand loyalty.…”
Section: Discussionsupporting
confidence: 92%
“…Laophon and Khamwon [64] identified that emotional brand attachment, directly and indirectly, affects brand advocacy. In a study by Natarajan and Veera Raghavan [65], shoppers' store attachment was found to positively affect various online brand advocacy behaviors. Thus, the following set of hypotheses: Hypothesis 4 (H4).…”
Section: Brand Attachmentmentioning
confidence: 99%
“…This paper points to insight into the behavior of Generation Z in Slovakia in purchasing used clothing using an analysis of categorical variables. Many consumers prefer shopping in the "online space" [42]. Gen Z has a lot of experience with digital knowledge [43], so this group of consumers is analyzed in this paper.…”
Section: Introductionmentioning
confidence: 99%